Reconstruction of the Concept of Emotional Boundaries in Surah ‎Maryam 19:41–47: An Analysis of Ijtima’i Exegesis and Bowen’s Family ‎Systems Theory - Muhammad Syukron Zun-Nurain; Kusnadi Kusnadi; Aristopan Aristopan; Nur Fitriyana (Jurnal Ulunnuha, 2026)
This study analyzes the reconstruction of the concept of emotional boundary in Surah Maryam (19:41–47) ‎through the al-adab al-ijtimā‘ī interpretive approach and Murray Bowen Bowen Family Systems Theory ‎‎(BFST). It is motivated by the increasing phenomenon of family estrangement, emotional cutoff, and no-‎contact practices in modern families caused by value conflicts and emotional distress. The study aims to ‎examine the construction of emotional boundary in Surah Maryam (19:41–47), reconstruct the Qur’anic ‎concept of relational boundaries, and relate it to BFST within contemporary family dynamics. This ‎research is a library study using tafsir ijtimā‘ī and contextual approaches. Primary data are drawn from ‎Tafsir Al-Mishbah by M. Quraish Shihab, supported by classical commentaries such as Jami' al-Bayan, Al-‎Jami' li Ahkam al-Qur'an, and Tafsir Ibn Kathir. The analysis involves textual examination of verses, ‎comparative exegesis, identification of relational values, and conceptual dialogue with BFST. The findings ‎show that Surah Maryam (19:41–47) constructs emotional boundary through empathetic communication, ‎emotional regulation, and firm faith commitment. Prophet Ibrahim (peace be upon him) maintains respect ‎while establishing boundaries when faith is threatened. The study formulates Peaceful No Contact as an ‎ethical and spiritual model of Qur’anic family relations